EFFECT OF SUBSTRATE MOISTURE CONTENT AND INVASIVE GRASS COMPETITION ON NATIVE FIG (Ficus fistulosa) SEEDLING RECRUITMENT IN LIMESTONE QUARRIES - Annisa Satyanti (SEAMEO BIOTROP, 2015)
This study was conducted to assess the potential use of the native fig (Ficus fistulosa) for rehabilitating degraded habitats in limestone quarry areas. A greenhouse experiment was performed to evaluate the effects of different substrate moisture levels and competition between the native fig (Ficus fistulosa) and the invasive grass Pennisetum polystachyon on the growth and survival of the native fig. Ficus fistulosa was selected as the study species because it exhibited the highest Importance Value Index (IVI) among other fig species recorded in the Ciampea limestone hill. The results showed that substrate moisture levels did not significantly affect fig biomass, and invasive grass biomass was not reduced under drought stress. However, the interaction between substrate moisture levels and competition with the invasive grass significantly reduced overall fig biomass, although it did not affect leaf number or individual plant size. This study suggests that successful quarry rehabilitation efforts should include invasive species management alongside soil treatment interventions.